Enhancement of Health-related Quality of Life among School-going Adolescent Girls with Improvement in Menstrual Hygiene Knowledge and Practices - Akanksha Goyal; Sunita Agarwal (Archives of Medicine and Health Sciences, 2024)
Background and Aim: In India, among adolescent girls, the problem associated with menstrual hygiene management (MHM) has a deep impact on health-related quality of life (HRQoL). Improvement in knowledge and menstrual hygiene practices may lead to enhancement in HRQoL. Therefore, the aim of the study was to enhance the HRQoL of adolescent school girls by improvement in menstrual hygiene knowledge and practices. Materials and Methods: The present study was an interventional, cross-sectional, questionnaire study conducted among adolescent school-going girls. The study was conducted among randomly selected five government secondary schools in Ajmer city and was conducted among adolescent girls of 7th–10th Class with the age group of 14–16 years. A total of 538 adolescent girls were surveyed in the pretest, and 503 was the sample size in the posttest with an attrition of 6.5%. Moreover, after the pretest, a workshop was conducted to educate adolescent girls about MHM. Results: A majority of the study participants (328 [61%]) had poor HRQoL after the pretest, which was improved to 195 (39%) of the study participants with good HRQoL after 3 months of the workshop during the posttest. The mean general health scores ([15.35 ± 0.38]) after 3 months of the workshop were significantly (P = 0.01*) higher among the study participants compared to the pretest scores ([10.93 ± 1.63]). Conclusion: From the above results, it has been concluded that there has been a significant improvement in knowledge, practice, and HRQoL among adolescent school-going girls of age 14–16 years when assessed after 3 months of the workshop on MHM.